Potencial de gestão comunitária de resíduos sólidos orgânicos no bairro Batista: Caçapava do Sul-RS - (:unkn) unknown (Universidade Federal do Pampa, 2020)
The increase in population, together with the increase in the consumption of products, leads to a large generation of municipal solid waste. In Brazil, the problem of solid waste has already taken on critical dimensions, where the urban population represents 84.35% of the total. There are more than 160 million inhabitants concentrating in the cities. The country generates about 214,868 tons of WR daily, this implies an average production of 1,035kg/inhabitant /da y (ABRELPE, 2017).On average, the household waste of Brazilians is composed of 51.4% of organic matter. Recycling organic waste and reestablishing its natural role of fertilizing soils is one of the major environmental challenges facing today. The most common organic waste recycling processes are composting and biodigestion. It is estimated that less than 2% of municipal solid waste is destined for composting. The general objective of this work is to analyze the potentialities of solid organic waste management in a neighborhood of the municipality of Caçapava do Sul - RS. The object of study chosen for analysis was the Batista neighborhood, located in the municipality of Caçapava do Sul. Taking into account the number of inhabitants of the municipality, 33,624, the volume of organic waste produced daily and the environmental and social problems that involve this theme, this research is extremely relevant. Regarding the methodology, for the collection of quantitative data of this research, documents from the Municipality of Caçapava do Sul – RS. The data were available from the year 2018. Surveys of municipal government costs were carried out with the shipment of this waste to landfill. In order to know the level of environmental awareness and the interest of the residents of the neighborhood for this theme, a questionnaire was electronically made available to the community. Among the participants, 79.9% reported not separating the garbage produced at home, 47.1% said do not do because do not think important. Another important fact is that 76.9% said that organic waste, the same destination as other waste, goes to the dump. The district under study has great potential for community management of solid organic waste, in view of the interest shown by the local population in the matter. However, environmental education work is needed with the local community.
Keywords: Educação Ambiental; Resíduos sólidos orgânicos; Destinação final; Environmental Education; Organic solid waste; Final destination; CNPQ::CIENCIAS EXATAS E DA TERRA